Threat or boost? Social comparison affects older people's performance differently depending on task domain - Swift, H. J. (2014)
Objectives. In this research, we investigate whether social comparison with younger people can result in either a stereotype-based threat or boost in older people's performance. Methods. Study I used nationally representative data to establish domains of performance in which older people are either stereotypically disadvantaged or advantaged relative to younger people. Study 2 was an experiment to test how a potentially threatening versus control versus enhancing comparison with younger people would affect performance in negatively and positively stereotyped task domains. Results. As predicted, compared with the control condition, stereotype threat caused performance decrements in both task domains. This effect was partially mediated by anxiety. Moreover, the enhancing social comparison boosted performance, but only on a crossword task, a task on which older people's abilities are favorably stereotyped. Discussion. The research demonstrates that a threatening comparison can result in underperformance by older people both in negatively and positively self-stereotyped task domains. It also demonstrates that social comparison with younger people can enhance older people's performance in a positively stereotyped task domain. The implications for creating circumstances likely to enable older people to achieve their full potential are discussed.